2022
DOI: 10.2196/32312
|View full text |Cite
|
Sign up to set email alerts
|

Digital Companion Choice to Support Teachers’ Stress Self-management: Systematic Approach Through Taxonomy Creation

Abstract: Background There are thousands of digital companions designed for emotional well-being and stress, including websites, wearables, and smartphone apps. Although public evaluation frameworks and ratings exist, they do not facilitate digital companion choice based on contextual or individual information, such as occupation or personal management strategies. Objective The aim of this study is to establish a process for creating a taxonomy to support systema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…Through the populated taxonomy [ 46 ], teachers were given the choice of technology for stress management and how this could support their self-care strategies. In accordance with self-determination theory (SDT) [ 109 ], this autonomy is a key motivator leading to engagement and, therefore, one possible explanation for the lack of attrition in this study, with no one abandoning their technology before their final interview.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the populated taxonomy [ 46 ], teachers were given the choice of technology for stress management and how this could support their self-care strategies. In accordance with self-determination theory (SDT) [ 109 ], this autonomy is a key motivator leading to engagement and, therefore, one possible explanation for the lack of attrition in this study, with no one abandoning their technology before their final interview.…”
Section: Discussionmentioning
confidence: 99%
“…It was recognized that, although this study did not seek to identify sources of stress, some of which could be outside the workplace, COVID-19 was adding a new source of stress for many that would have to be acknowledged. Teachers were then presented with a rigorously compiled taxonomy, the design of which has been described elsewhere [ 46 ]. The taxonomy enabled teachers to have some limited choice regarding the technology they were to use for the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that the MARS scale demonstrates good validity and reliability, making it a reliable measurement tool [30][31][32][33][34]. The uMARS scale, developed by Manning et al [36], serves as an extension of the original MARS scale, specifically designed to prioritize the assessments of average users toward mobile apps.…”
Section: Evaluation Toolmentioning
confidence: 99%
“…The concept of digital companions for maintaining a healthy lifestyle and goal achievement is increasingly gaining attention; it is, for example, applied and studied in the context of professional work support, education, stress management, healthcare, and behavior change (Jang and Kim, 2020 ; Braun et al, 2021 ; Spirig et al, 2021 ; Weber et al, 2021 ; Manning et al, 2022 ). All the facets, however, converge on similar topics, such as assessing the user's context or learning more about the user's habits in the interest of providing personalized support to address a specific problem.…”
Section: Background and Related Workmentioning
confidence: 99%